Perbedaan Somatometri Itik Tegal, Itik Magelang Dan Itik Pengging - Desi Wulandari; S Sunarno; Tyas Rini Saraswati (Jurnal Akademika Biologi, 2015)
Local ducks in Indonesia there are several kinds, for example Tegal ducks, Magelang ducks and Pengging duck each having characteristics different somatometri. Research on somatometri ducks that includes body weight, leg length, beak length, wing length, body length, and long-neck ducks important to know somatometri of each duck. This study aimed to analyze the differences somatometri at Tegal ducks, Magelang ducks and Pengging duck, which includes weight, leg length, beak length, wing length, body length, and a long neck. Ducks were used in this study maintained in the Central Breeding and Raising Ducks Work Unit Non Ruminant Livestock Banyubiru, Ambarawa. The study was conducted by measuring somatometri of each six monthold ducks. Duck samples taken from three different types of ducks that Tegal duck, Pengging duck and Magelang duck, of each type of sample taken many ducks as 6 tails. Data were analyzed using analysis of variance (ANOVA) with the differentiating factor is the type of duck. If the data were analyzed contained a real difference, then do a further test using the test Least Significant Differences (LSD) at 95% confidence level. The results showed that there was no significant difference in all parameters of the study. Conclusion of the study three types of ducks will have somatometri not unlike that includes, weight, leg length, beak length, wing length, body length and the length of the neck. It was because give feed and feed same time. Keywords: Local Ducks in Central Java, Somatometri, Tegal ducks, Magelang ducks, Pengging duck